Assessment of Brand as Economic Value Asset - Rianto, Fera Puspita (KnE Social Sciences, 2023)
This study aims to explore how to create economic value for a brand and determine the competent authority responsible for its valuation. The assessment of economic value, especially for brands, requires special provisions and regulations regarding Intellectual Property Rights (IPR). Trademark rights are valuable assets that need to be recognized as such. Technological advancements have spurred economic growth in the creative industry, leading to competition in creating valuable and useful works. A brand serves as an identity, feature, icon, and representation of a product. Its economic value and popularity increase significantly when used by individuals with a large number of followers. To protect the brand’s recognition, it must be officially registered, preventing others from easily claiming it as their own. However, currently, there is no specific government regulation governing the economic valuation of a brand. Therefore, it becomes essential for the government to play a role in regulating this aspect. Regulations concerning the economic valuation of a brand become crucial when the brand is utilized as collateral for debt, becomes subject to disputes, or is considered as an asset in the event of bankruptcy. The research adopts a normative juridical approach, examining theories, principles, and related regulations relevant to the topic. Additionally, a quantitative method is used to analyze social reality and human behavior objectively and measure them based on the existing problems in this area. Keywords: brand, economic value, guarantee, asset